Role of the television broadcasting in the construction of image : image of Turkey in Colombia due to the Turkish series - Navarrete, Nathalia Arango (My University, 2020)
Son birkaç yıldır Latin Amerika'da Türk dizilerinin izlenme oranlarında büyük bir artış oldu ve Kolombiya istisna değil. Ülke, sabah ve öğleden sonraki yayın ajandalarında Türk dizilerine yer açmak için kendi prodüksiyonlarını önemli ölçüde azalttı. Ulusal televizyonların yabancı dizilerin akınına uğraması,Türkiye ve Türklerin daha fazla tanınmasını sağladı; bu nedenle, Güney Amerika ülkesinde bir Türkiye imajı oluştu.Bu tezin konusu, Türkiye'nin başarmayı amaçladığı yumuşak güçle bağlantılı olarak küreselleşme sürecinde kitle iletişim araçlarının etkisini araştırmaktır ve bu bağlamda televizyonun oynadığı temel rolü açıklamayı amaçlamaktadır. Birinci bölümde okuyucu, siyasi ve kültürel küreselleşme ve mevcut çağda kamu diplomasisinin önemi üzerine kısa bir bilimsel inceleme bulacaktır. İkinci bölüm, televizyona ve özellikle ABD yapımlarının dünya çapındaki izleyicilere ulaşmasının hızlanmasına odaklanıyor. Daha sonra Latin Amerika televizyonlarının kapılarının Türk dizilerine nasıl açılacağını ve bu yapımların Amerika Kıtası’na ulaşmadan önce Ortadoğu ve Balkanlar'da izledikleri yolu anlatıyor. Ücüncü bölüm, 364 kişiye uygulanan bir anketle Kolombiyalıların Türkiye ve Türkler hakkındaki gerçek imajını araştırıyor. Anket, Türkiye'nin yumuşak gücünün gerçek bir etki yaratıp yaratmadığını ve Türk yapımlarının bir imaj oluşturup oluşturmadığını cevaplamaya yöneliktir.

In the last few years there has been a boom of Turkish series in Latin America and Colombia is not the exception. The country has significantly reduced its own production broadcasting in order to give space to the Turkish soap operas in the morning and afternoon agenda. The incursion of foreign shows in the national television has brought a larger acknowledge of Turkey and the Turks; therefore, an image has been portrayed in the South American country. This research interest is to explore the concepts of globalization and mass media in relation to the soft power Turkey is aiming to achieve and intends to explain the main role television plays in this scenario. In the first chapter the reader will find a brief dissertation on political and cultural globalization and the importance of public diplomacy in the current era. The second chapter focuses on television and particularly in the boost of the USA production reaching worldwide audiences; later on a summary of Latin American television to explain how the door to Turkish series could be open and ends by portraying the path these productions have followed through the Middle East and the Balkans before reaching the American continent. The last one delves into the actual image Colombians have about Turkey and Turks with a survey that was applied to 364 people and is directed to answer if the soft power exerted a real impact and if the Turkish productions did create an imaginary.
Keywords: Gazetecilik; Journalism; kültürel küreselleşme kamu diplomasi yumuşak gücü televizyon cultural globalization public diplomacy soft power television